History, literature, and narration (2008)
In the second half of the twentieth century, the philosophy of history came to recognize the irreducibly narrative character of history. This underlined the differences between history and science and highlighted its affinities with literature. This article suggests some criteria by which history can be distinguished from literature without undermining the narrative character of the former and recognizing that both are deeply anchored in the structures of the consciousness of time. The text has three parts. The first reconstructs Danto's argument in favor of the narrative character of history. The second critiques White's position regarding the problematic border between history and literature. With the assistance of Gadamer and Koselleck, the final section shows how the reconstruction of historical facts and the literary exploration of the human condition are two modalities of a wider task related to the study of the structures of temporality.